Tillage operation and fertilizer management effect on yield of boro rice in saline prone zone of Bangladesh - Ali, MI; Islam, MS; Hossain, MS; Azad, MAK (Bangladesh Journal of Nuclear Agriculture, 2023)
A field experiment was conducted at Shyamnagar Satkhira during Boro season in two consecutive year 2019-20 and 2020-21 to find out the suitable tillage operation as well proper doses of farmyard manure (FYM) for increasing yield of rice under natural salinity condition. The experiment was laid out in split plot design assigning tillage operations in the main plot and FYM in the sub plot with three replications. Four tillage operations and six doses of FYM were used. Among the treatments, land ploughed at 20 cm depth with five times produced the highest grain yield (6.63 t ha-1) and application of FYM at the rate of 5.0 t ha-1 produced the highest grain yield (5.89 t ha-1) in 2019-20. Land ploughed at 20 cm depth with five times produced the highest grain yield (6.65 t ha-1) where FYM at 5 t ha-1 produced the highest grain yield (6.21 t ha-1) in 2020-21. The effect of tillage 20 cm depth five times and FYM 5.0 t ha-1 produced the highest grain yield (6.84 t ha-1) in both the season 2019-20 and 2020-21. This study showed that tillage operation and application of farmyard manure (FYM) at suitable dose amends the saline soil and increase the yield and yield attributes of Boro rice in saline soil. Bangladesh J. Nuclear Agric, 37(1): 51-62, 2023